2000
DOI: 10.1063/1.1290477
|View full text |Cite
|
Sign up to set email alerts
|

Effect of electrostatic interactions on the dynamics of semiflexible monodisperse DNA fragments

Abstract: The dynamics of three monodisperse linear duplex DNA fragments—a 2311 base pair restriction fragment and 1500 and 1100 base pair polymerase chain reaction fragments—in dilute solution are studied as functions of added salt (NaCl) concentration by dynamic light scattering-photon correlation spectroscopy. Translational diffusion coefficients and intramolecular relaxation times are extracted from the measured light scattering intensity time autocorrelation functions as the added salt concentration is reduced from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
31
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 46 publications
9
31
0
Order By: Relevance
“…Evidences for the effect of the salt concentration on DNA hydrodynamic radius were produced by Newman et al [34] and Liu et al [35] but only for DNA fragments shorter than 2300 bp and, in this case, the observed variation of hydrodynamic radius is much less pronounced than in the coil-globule transition case and in our case too. At present no systematic studies have been carried out to understand the effect of ionic strength for DNA molecules longer than few thousand bp.…”
Section: Discussionsupporting
confidence: 46%
“…Evidences for the effect of the salt concentration on DNA hydrodynamic radius were produced by Newman et al [34] and Liu et al [35] but only for DNA fragments shorter than 2300 bp and, in this case, the observed variation of hydrodynamic radius is much less pronounced than in the coil-globule transition case and in our case too. At present no systematic studies have been carried out to understand the effect of ionic strength for DNA molecules longer than few thousand bp.…”
Section: Discussionsupporting
confidence: 46%
“…While there has been a number of DLS reports on the properties of DNA solutions (see, for example Refs. [71][72][73][74]), studies involving interactions between DNA and cationic amphiphiles are in a very limited number [18,24,75].…”
Section: A Dynamic Light Scattering Studymentioning
confidence: 99%
“…Stiff rodlike particles experience a considerably larger Stokes drag. Earlier sedimentation [9,17] as well as translational diffusion [10,11] measurements on monodisperse DNA fragments of up to 2311 bp have shown that the Stokes drag is predicted correctly by the Yamakawa-Fujii [18] theory for smooth wormlike cylinders without excluded volume and neglecting endeffects. The orientationally averaged friction coefficient of a wormlike Brownian cylinder of contour length L c , diameter D, and persistence length q resembles the friction factor for a sphere but contains an additional term, F (D, L c , q), that is affected by the actual shape [18]:…”
Section: Sedimentation Of Non-interacting Semiflexible Polymersmentioning
confidence: 84%
“…Several studies have addressed static properties of DNA solutions, including the molecular conformation and intermolecular interactions [2][3][4][5] and mesophase formation [6][7][8]. Transport properties investigated include mutual diffusion [3][4][5][9][10][11], self-diffusion [12], rotational diffusion [13][14][15], rheology [5,16], and sedimentation [9,17]. A systematic study of the length and concentration dependence of the transport properties of DNA molecules and a comparison with theoretical models for semiflexible polymers is, however, still lacking.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation